Mechanics of the giant circle on high bar - Hiley, M. J. (University Loughborough, 1998)
In Men's Artistic Gymnastics the accelerated backward giant circle on high bar is used to generate the rotation required for the subsequent skill. When used prior to a dismount at the end of a high bar routine the gymnast performs a number of backward giant circles in order to generate sufficient rotation to perform the dismount. The most common dismounts from high bar require the gymnast to perform two backward somersaults in the layout position. Of all the dismounts performed by elite male gymnasts it is the double layout somersault dismount which requires the most rotation. Observations of elite gymnasts have shown that two different techniques may be adopted in the accelerated giant circle performed before release. Since gymnasts are able to perform the dismount from both types the question arises: What is the best technique for increasing rotation using accelerated backward giant circles?